1995
DOI: 10.1182/blood.v86.12.4638.bloodjournal86124638
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor prevents apoptosis of rat peritoneal mast cells through the trk proto-oncogene receptor

Abstract: We investigated the inhibitory activity of nerve growth factor (NGF) on apoptosis of rat peritoneal mast cells (PMCs) and compared it with that of recombinant stem cell factor (rSCF), which is a mast cell growth factor. When PMCs were incubated up to 72 hours in the presence of control medium, internucleosomal fragmentation of DNA indicating apoptosis was detected by agarose gel electrophoresis and flow cytometry. The aged PMCs showed morphological changes typical for apoptosis, such as chromatin condensation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 29 publications
4
46
0
Order By: Relevance
“…In this study, to check the survival promoting effect of NGF on human mast cells, we investigated the expression of speci®c receptors for NGF on the surface of cord bloodderived human cultured mast cells and a biological activity of NGF for the survival of the cells. The analysis using RT-PCR and¯ow cytometry showed that p140 trk but not p75 LNGFR was expressed on cord blood-derived human cultured mast cells, and immunoprecipitaion and western blot analysis revealed that NGF elicited a rapid phosphorylation of p140 trk on tyrosine residue of the cells, in accordance with the ®ndings on rodent mast cells [20] and recent reports on human mast cells [21,22]. Then we demonstrated that the pretreatment with K252a, a tyrosine kinase inhibitor, inhibited p140 trk kinase activity, suggesting that the effect of NGF was mediated through the p140 trk , as previously described in rat PMC [20].…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…In this study, to check the survival promoting effect of NGF on human mast cells, we investigated the expression of speci®c receptors for NGF on the surface of cord bloodderived human cultured mast cells and a biological activity of NGF for the survival of the cells. The analysis using RT-PCR and¯ow cytometry showed that p140 trk but not p75 LNGFR was expressed on cord blood-derived human cultured mast cells, and immunoprecipitaion and western blot analysis revealed that NGF elicited a rapid phosphorylation of p140 trk on tyrosine residue of the cells, in accordance with the ®ndings on rodent mast cells [20] and recent reports on human mast cells [21,22]. Then we demonstrated that the pretreatment with K252a, a tyrosine kinase inhibitor, inhibited p140 trk kinase activity, suggesting that the effect of NGF was mediated through the p140 trk , as previously described in rat PMC [20].…”
Section: Discussionsupporting
confidence: 60%
“…Although combination of rhSCF and rIL-6 induced active DNA synthesis, no signi®cant changes on DNA synthesis were observed by the addition of NGF, suggesting that NGF does not have a proliferating activity to human mast cells. We also ascertained that NGF alone could not prevent apoptosis of the cultured human mast cells, unlike rat PMC, of which NGF alone has been reported to support the viability [20]. In contrast, the addition of NGF to the medium containing rhSCF showed a signi®cant inhibitory effect on the apoptosis of the human cultured mast cells.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations